The architect's apprentice - Shafak, Elif (Penguin Books, 2015)
When Jahan travels to 16th-century Istanbul as a stowaway, with the gift of a white elephabt for the Sultan, little does he anticipate the journey on which he is about to embark. Whispers in the palace gardens and secret journeys through Istanbul lead him to Mihrimah, the beautiful princess. Still under her spell, he is promoted from simple mahut to apprentice of the royal architect, Sinan - when his fortunes take a mysterious change.